Intramolecular Photogeneration of a Tyrosine Radical in a Designed Protein. Issue 3 (8th February 2017) - Tebo, Alison G.; Quaranta, Annamaria; Herrero, Christian; Pecoraro, Vincent L.; Aukauloo, Ally
Abstract: Long‐distance biological electron transfer occurs through a hopping mechanism and often involves tyrosine as a high potential intermediate, for example in the early charge separation steps during photosynthesis. Protein design allows for the development of minimal systems to study the underlying principles of complex systems. Herein, we report the development of the first ruthenium‐linked designed protein for the photogeneration of a tyrosine radical by intramolecular electron transfer. Abstract : Model behavior : A designed protein has been covalently modified with a ruthenium polypyridine chromophore. Photoinduced intramolecular electron transfer from the attached ruthenium polypyridine chromophore provides a good model for protein‐based tyrosine radicals.